Pengaruh Penerapan Tata Tertib Sekolah terhadap Disiplin Belajar Siswa - Rohmat Alimun Taha; I Nyoman Sujana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This study aims to examine the influence of school discipline conducted on the student's learning discipline. This study is a type of clausal study which determines the relationship between both two variables. There are two variables in this study: variable X or school discipline and variable Y or students’ learning discipline. This study involved the students at MA Al-Irsyad Candikuning II Bedugul. In this study, the population and samples were 76 people who were from students in grades X, XI, and XII MA Al-Irsyad Candikuning II Bedugul. Data collection with questionnaires distributed throughout the respondents is related to the influence of school discipline. The data in which the results were analyzed used simple linear regression analysis. This study's results are directed, namely the good and positive influence of school discipline where students study at MA Al-Irsyad Candikuning II Bedugul. The study proved by the results of school discipline influenced 22.2% towards the students’ learning discipline.